Higher coronary calcium score is associated with increased risk of atrial fibrillation recurrence. (19th May 2022) - Fernandes, S; Ladeiras-Lopes, R; Cruz, I; Silva, G; Diaz, S; Barros, A; Saraiva, F; Faria, R; Almeida, J; Fonseca, P; Goncalves, H; Oliveira, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with atrial fibrillation (AF) referred for catheter ablation routinely undergo cardiac computed tomography (CCT) for procedure planning. An opportunistic evaluation of coronary artery calcium score (CACS) can be an important tool to improve clinical care. It is already known that CACS is associated with a high risk of AF development, particularly if values are above 100, but few data are available regarding the impact of CACS in AF recurrence after ablation. Purpose: To assess the impact of CACS on atrial fibrillation recurrence following catheter ablation. Methods: Retrospective, single-centre cohort study of consecutive patients with AF undergoing CCT for ablation procedure planning, from 2017 to 2019. Baseline clinical and demographical data were collected. Patients with known history of coronary artery disease (CAD) and moderate to severe valvular heart disease were excluded. CACS was assessed using the Agatston method. Recurrence was defined as any documented episode of AF, atrial flutter or atrial tachycardia after 3 months from procedure. Patients were stratified in CACS<100 and CACS≥100. Explorative analysis incorporated Kaplan-Meier survival curves and Cox regression. Results: A total of 354 patients were included, with a mean age of 56 ± 12 years, 66% male and 21% with persistent AF. More than half of the patients had a CACS>0 (n=185, 52%) and 63 patients (18%) had a CACS≥100. Patients with CACS≥100 were older (63 ± 7 vs 54 ± 12 years, p<0.001), had higher prevalence of hypertension (68% vs 43%, p<0.001) and diabetes mellitus (21% vs 10%, p=0.012) and higher left atrial volume (39 ± 9 vs 35 ± 9 ml/m2, p=0.018). After a median observation time of 34 months (IQR 24-43), 117 patients (33%) had AF recurrence. CACS≥100 was associated with increased risk of AF recurrence (unadjusted Cox regression: hazard ratio [HR] 1.85; 95% confidence interval [CI], 1.23-2.79, p=0.003) (Fig. 1). After covariate adjustment (age, gender, hypertension, diabetes mellitus, obesity, thyroid disease, AF type and left atria enlargement) CACS≥100 remained an independent predictor of the risk of AF recurrence (HR, 1.68; 95% CI, 1.05-2.70, p=0.03) as well as persistent AF (HR, 1.91; 95% CI, 1.23-3.00, p=0.004) (Fig. 2). Conclusion: In patients with AF undergoing catheter ablation, without previous history of CAD, a CACS≥100 was independently associated with a 68% increase in the risk of AF recurrence.